Desenvolvimento de um módulo para variação da tensão RMS aplicada em ventiladores por comando de sinal de radiofrequência - Morikawa, Mateus (2022)
The smart home concept has been gaining popularity and becoming even more accessible for those who want to delight in its benefits. Advances in technology have been permitting cost reduction in some electronic devices. Furthermore, the wireless technology facilitates the process of making a smart home. RF devices can receive commands from virtual assistants through voice commands, making daily activities, such as turning a home appliance on and off, even more convinient. This ability to use voice commands to give instructions to the house could be helpful for people with some motor disability. In this sense, the present work aims to develop a module to vary fans speed through RF signal. In conclusion, the simulation and hands-on results herein reported showcases the proposed system functionality.